2022
DOI: 10.1002/marc.202200320
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive P(AAc‐co‐NIPAm) Hydrogels Display Enhanced Toughness and Self‐Healing via Ion–Ligand Interactions

Abstract: Hydrogels containing thermosensitive polymers such as poly(N‐isopropylacrylamide) (P(NIPAm)) may contract during heating and show great promise in fields ranging from soft robotics to thermosensitive biosensors. However, these gels often exhibit low stiffness, tensile strength, and mechanical toughness, limiting their applicability. Through copolymerization of P(NIPAm) with poly(Acrylic acid) (P(AAc)) and introduction of ferric ions (Fe3+) that coordinate with functional groups along the P(AAc) chains, here a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These results indicated that the tensile strength decreased with increasing FeCl 2 concentration, and the elongation at break increased with increasing FeCl 2 concentration. The main reason for this phenomenon was that FeCl 2 acted as a bridge in the composite hydrogel, which could enhance the ductility; 35 and Fe 2+ addition also resulted in increasing water content and formation of more hydrogen bonds, which provided an effective energy dissipation path and enhanced the elongation at break. 36,37 The variation in the EMI shielding efficiency as a function of C-MXene nanosheet and FeCl 2 concentrations for the resultant hydrogels are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the tensile strength decreased with increasing FeCl 2 concentration, and the elongation at break increased with increasing FeCl 2 concentration. The main reason for this phenomenon was that FeCl 2 acted as a bridge in the composite hydrogel, which could enhance the ductility; 35 and Fe 2+ addition also resulted in increasing water content and formation of more hydrogen bonds, which provided an effective energy dissipation path and enhanced the elongation at break. 36,37 The variation in the EMI shielding efficiency as a function of C-MXene nanosheet and FeCl 2 concentrations for the resultant hydrogels are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The simplicity and robustness of this approach, combined with its compatibility with other first-order physical phenomena, may render it useful for predictive design of diverse hybrid networks including elastomers with charge interactions, 16,65,66 vitrimers, 6 and metallopolymers. 7,9 Therefore, in future work, this method may be utilized in conjunction with additional modeling approaches for other significant phenomena (e.g., entanglement, reptation, etc.) to investigate polymer micromechanics or guide design applications.…”
Section: Discussionmentioning
confidence: 99%
“…To amend the rule of mixture we posit that some fraction, x, of stable bonds in hybrid networks relax at rate k d due to reconfiguration of adjacent dynamic bonds, whereas the fraction 1 À x cannot relax over intermediate timescales because they are constrained by the stable bond network structure, suffer from relaxation retardation due to bond lifetime renormalization effects, 33,35 or are otherwise constrained by steric interactions (as in the case of the 2D, highly packed networks observed in the current discrete model). Incorporating x into eqn (9), gives a coupled rule of mixture for hybrid networks:…”
Section: Coupling Between Bond Types Mediates Relaxationmentioning
confidence: 99%
See 2 more Smart Citations